﻿New nematode Tahamina indica gen. nov., sp. nov. (Nematoda, Dorylaimida, Tylencholaimoidea) from the tropical rainforest, Western Ghats - Md Niraul Islam; Wasim Ahmad (ZooKeys, 2023)
During a nematological survey in the Western Ghats a new nematode belonging to the superfamily Tylencholaimoida (Dorylaimida) extracted from the rhizosphere of the soil of grasses, is described and illustrated. Tahamina indica gen. nov., sp. nov. is characterized by females with a body length of 1.3–1.4 mm; lip region 8.0 μm wide, approximately one-fourth of the body diameter at the pharyngeal base; amphidial fovea cup-shaped, about one-half as wide as the lip region diameter. Odontostyle 8.0–9.0 μm long, 1.0–1.1 times lip region diameter; guiding ring simple; odontophore rod-like, 10.5–11.5 μm long with basal thickening or minute knobs-like structure; pharynx consisting of a weakly muscular anterior part, expanding abruptly into a cylindrical basal bulb, occupying about two-fifths to one-half of the total pharyngeal length; female genital system monodelphic-opisthodelphic with anterior uterine sac; vulval opening pore-like, and tail elongated with a slight dorsally curved tip. Males not found.